2018
DOI: 10.1101/448068
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Coping with strangers: how familiarity and active interactions shape group coordination inCorydoras aeneus

Abstract: Social groups whose members have had sustained prior experience with each other frequently exhibit improved coordination and outperform groups whose members are unfamiliar with one another. The mechanisms by which familiarity assists coordination are not well known. Prior social experience may simply allow individuals to learn the behavioral tendencies of familiar group-mates and coordinate accordingly. In the absence of prior social experience, it would be adaptive for individuals to develop strategies for co… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
2

Year Published

2018
2018
2019
2019

Publication Types

Select...
2
1

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(14 citation statements)
references
References 15 publications
1
11
2
Order By: Relevance
“…Fishes that do not interact tactilely are not known to bump into one another, even during large, dynamic shoaling movements (Katz et al, ), and none of the Bronze Cory catfish in this study (or in any of our previous studies) collided with objects in their enclosures or the walls of their tanks, even when placed in novel environments (as were the fish in this study). While it cannot be excluded with absolute certainty that some tactile interactions were the result of unintentional collisions between individuals, we have also shown in previous studies that the frequency of interactions is affected by familiarity in a foraging setting, which adds support to our interpretation that nudging is a directed, intentional interaction between individuals (as in Riley et al, ). Consequently, we are confident in our assessment of nudging as a discrete social interaction that individuals utilize in a variety of contexts, with the current study focusing on its role in the context of group flight responses.…”
Section: Methodssupporting
confidence: 87%
See 4 more Smart Citations
“…Fishes that do not interact tactilely are not known to bump into one another, even during large, dynamic shoaling movements (Katz et al, ), and none of the Bronze Cory catfish in this study (or in any of our previous studies) collided with objects in their enclosures or the walls of their tanks, even when placed in novel environments (as were the fish in this study). While it cannot be excluded with absolute certainty that some tactile interactions were the result of unintentional collisions between individuals, we have also shown in previous studies that the frequency of interactions is affected by familiarity in a foraging setting, which adds support to our interpretation that nudging is a directed, intentional interaction between individuals (as in Riley et al, ). Consequently, we are confident in our assessment of nudging as a discrete social interaction that individuals utilize in a variety of contexts, with the current study focusing on its role in the context of group flight responses.…”
Section: Methodssupporting
confidence: 87%
“…The nature of this behaviour, a tactile nudge, perhaps lends itself to maintaining cohesion, as the initiator must be in such close physical proximity as to touch the receiver of its nudge (for an example of this behaviour, please see the video in the Appendix S1). Although the current study does not definitively elucidate a causal link between nudging and increased cohesion, our previous work showed that, under nonthreatening conditions, unfamiliar fish achieve high levels of cohesion through increased rates of nudging compared to familiar fish, which exhibit high cohesion with comparatively low levels of nudging (Riley et al, ). This suggests that nudging is a directed social behaviour that is influenced by familiarity and context, and not a mere consequence of proximity.…”
Section: Discussionmentioning
confidence: 57%
See 3 more Smart Citations